P8 Pooled analysis of data from the TOMORROW and INPULSIS® trials of nintedanib in IPF. (12th November 2015) - Richeldi, L; Brown, KK; Cottin, V; Selman, M; Kimura, T; Stowasser, S
Abstract : Background: The 52-week, Phase II TOMORROW trial and two replicate 52-week, Phase III INPULSIS® trials investigated the efficacy and safety of nintedanib 150 mg twice daily (bid) versus placebo in patients with idiopathic pulmonary fibrosis (IPF). Aim: A pooled analysis of data from the TOMORROW and INPULSIS® trials was conducted to obtain a more precise estimate of the treatment effect of nintedanib. Methods: Results for annual rate of decline in forced vital capacity (FVC), time to first investigator-reported acute exacerbation, change from baseline in St George's Respiratory Questionnaire (SGRQ) total score and mortality over 52 weeks were analysed. Results: 1231 patients (nintedanib 150 mg bid n = 723, placebo n = 508, reflecting the 3:2 randomisation in the INPULSIS® trials) were included. Baseline characteristics were comparable between treatment groups and across trials. The overall adjusted annual rate of decline in FVC was −112.4 mL/year with nintedanib and −223.3 mL/year with placebo (difference: 110.9 mL/year [95% CI: 78.5, 143.3]; p < 0.0001). The overall hazard ratio for time to first acute exacerbation was 0.53 (95% CI: 0.34, 0.83; p = 0.0047) in favour of nintedanib. The overall adjusted mean change from baseline in SGRQ total score at week 52 was 2.92 with nintedanib and 4.97 with placebo (difference: −2.05 [95% CI: −3.59, −0.50; p = 0.0095]). Hazard ratios for time to all-cause and on-treatment mortality were 0.70 (95% CI: 0.46, 1.08; p = 0.0954) and 0.57 (95% CI: 0.34, 0.97; p = 0.0274), respectively, in favour of nintedanib. Conclusion: Pooled data from the TOMORROW and INPULSIS® trials confirm a significant beneficial effect of nintedanib on reducing disease progression in patients with IPF.